Kinetic modeling of the enzymatic hydrolysis of proteins of visceras from red tilapia (Oreochromis sp.): effect of substrate and enzyme concentration - ZAPATA-MONTOYA, José Edgar; GIRALDO-RIOS, Diego Enrique; BAÉZ-SUAREZ, Andrea Johana (Vitae, 2018)
Background: the growth of world aquaculture has generated important environmental impacts as discard residues that are important sources of protein, which has been used to manufacture low-value products, such as animal food, fish flour and fertilizers. Objectives: to evaluate the effect of enzyme and substrate concentration on the degree of hydrolysis (DH) of proteins in the red tilapia (Oreochromis sp.) viscera (RTV). Methods: the commercial alcalase 2.4 L enzyme was used at different concentrations to hydrolyse the proteins in RTV at 53.5°C and a pH of 9.5 in a 1 L magnetically stirred, jacketed, glass batch reactor connected to an automatic titrator. Each experiment was conducted over 6 h in which every consumed volume of base was recorded every 5 min to determine the corresponding DH at each point. Results: the results indicated that increasing the enzyme concentration produced an increase in the DH and in the reaction rate, while increasing the substrate concentration produced a decrease in both parameters. For this reason, a mathematical model was adjusted for the inhibition of substrate from the exponential kinetic equation d(DH)/dt = a*EXP[-b*(DH)] to explain the behavior of the DH as a function of substrate concentration in this hydrolytic process. The parameters a and b were estimated from a nonlinear regression. Based on these results, the reaction constants were determined as Ks = 456.75 g L-1, K2 = 1.2191 min-1, Kd = 0.2224 min-1, KM = 1.8963 and K3 = 0.1173 L g-1 min-1, which allowed the generation of a good correlation between the predicted and experimental values at the different evaluated operating conditions. This correlation was supported by a low average relative error (ARE) of 3.26%. Conclusion: under evaluated experimental conditions, the kinetics of the hydrolysis reaction followed a substrate inhibition mechanism without product inhibition, which was adjusted through a typical exponential Equation that involves two parameters (a and b) associated with the kinetic constants (Ks, K2, and Kd).